Performance of Retrofitted Square Reinforced Concrete Column using Wire Mesh and SCC Subjected to Cyclic Load - Hence M. Wuaten; Herman Parung; A. Arwin Amiruddin; Rita Irmawaty (Civil Engineering Journal, 2021)
One way to restore or increase the strength of the structure against earthquakes is to use retrofit method and wire mesh is a material that has high prospects as retrofit material. The purpose of this study was to examine the use of wire mesh as a retrofit material on reinforced concrete columns burdened with cyclic loads. In this study, testing of 3 square column samples of reinforced concrete with dimensions of 300  300 mm. The first specimen is fully retrofit on the entire cross-section of the column, the second specimen is retrofitted on the plastic hinge area of the column and the third specimen is a control column without retrofit. In the first and second specimens were retrofitted with wire mesh size M6 using SCC which was then tested with a cyclic load using displacement control method based on the provisions stipulated in the Indonesian Standard SNI 7834:2012. From the test results and analysis results, it was found that the capacity and ductility of displacement in retrofit specimens increased significantly compared to specimens that were not retrofit. In addition, the decrease in stiffness in retrofit specimens was smaller than in non-retrofit specimens. As for the value of energy dissipation in fully retrofit specimens and in retrofit on the plastic hinge area is almost close. Based on these conditions, the use of wire mesh size M6 and SCC can be used as retrofit material on the column that is burdened with cyclic load. Doi: 10.28991/cej-2021-03091685 Full Text: PDF